The Role of Curcumin in Modulating Colonic Microbiota During Colitis and Colon Cancer Prevention. Issue 11 (November 2015) - McFadden, Rita-Marie T.; Larmonier, Claire B.; Shehab, Kareem W.; Midura-Kiela, Monica; Ramalingam, Rajalakshmy; Harrison, Christy A.; Besselsen, David G.; Chase, John H.; Caporaso, J. Gregory; Jobin, Christian; Ghishan, Fayez K.; Kiela, Pawel R.
Abstract : Background: Intestinal microbiota influences the progression of colitis-associated colorectal cancer. With diet being a key determinant of the gut microbial ecology, dietary interventions are an attractive avenue for the prevention of colitis-associated colorectal cancer. Curcumin is the most active constituent of the ground rhizome of the Curcuma longa plant, which has been demonstrated to have anti-inflammatory, antioxidative, and antiproliferative properties. Methods: Il10 −/− mice on 129/SvEv background were used as a model of colitis-associated colorectal cancer. Starting at 10 weeks of age, wild-type or Il10 −/− mice received 6 weekly intraperitoneal injections of azoxymethane (AOM) or phosphate-buffered saline (PBS) and were started on either a control or a curcumin-supplemented diet. Stools were collected every 4 weeks for microbial community analysis. Mice were killed at 30 weeks of age. Results: Curcumin-supplemented diet increased survival, decreased colon weight/length ratio, and, at 0.5%, entirely eliminated tumor burden. Although colonic histology indicated improvement with curcumin, no effects of mucosal immune responses have been observed in PBS/ Il10 −/− mice and limited effects were seen in AOM/ Il10 −/− mice. In wild-type and in Il10 −/− mice, curcumin increased bacterial richness, prevented age-related decrease in alpha diversity, increased the relative abundance of Lactobacillales, and decreased Coriobacterales order. Taxonomic profile of AOM/ Il10 −/− mice receiving curcumin was more similar to those of wild-type mice than those fed control diet. Conclusions: In AOM/ Il10 −/− model, curcumin reduced or eliminated colonic tumor burden with limited effects on mucosal immune responses. The beneficial effect of curcumin on tumorigenesis was associated with the maintenance of a more diverse colonic microbial ecology. Abstract : Article first published online 25 July 2015.Supplemental Digital Content is Available in the Text.